4,4'-dicloro-difenil disseleneto reverte o déficit de memória induzido pela corticosterona em camundongos - Zborowski, Vanessa Angonesi (2016)
Chronic stress or even a single serious traumatic experience may have a negative impact on cognitive function. In this sense, organic selenium compounds are molecules that arouse great interest because they have various protective effects on memory deficits already reported in different experimental models. The present study investigated the effect of administration of p-chloro-diphenyl diselenide (p-ClPhSe)2 in the memory impairment related to stress induced by exposure to corticosterone in mice and the action mechanisms involved. Male adult Swiss mice were divided into six groups: (I) mineral oil and (II and III) (p-ClPhSe)2 at a dose of 1 or 5 mg/kg, these groups received the corticosterone vehicle (1% ethanol / H20) in drinking water; group (IV) received mineral oil and (V and VI) were given (p-ClPhSe)2 at both doses and corticosterone in the drinking water. The animals received vehicle or corticosterone (1% ethanol/H20) by four weeks in drinking water. In the last week of corticosterone treatment once a day with (p-ClPhSe)2 at a dose of 1 or 5mg/kg or mineral oil (10ml/kg) by the intragastric route. After that, behavioral tests such as object recognition test (ORT), object location test (OLT), step-down passive avoidance (SDPA) were perfomed. The locomotor and exploratory activities of mice were also evaluated. The toxicity of (p-ClPhSe)2 was investigated by determining the activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT), and the levels of urea, total cholesterol, triglycerides and high-density lipoprotein (HDL) in the plasma of mice. Samples of cerebral cortex and hippocampus were obteined to determine the activities of Na+K+ATPase and acetylcholinesterase (AChE) and glutamate uptake. The results demonstrated that the treatment with (p-ClPhSe)2 at both doses was effective in reversing memory deficits in the ORT, OLT and SDPA induced by corticosterone in mice. In addition, both doses of (p-ClPhSe)2 reversed the increase in glutamate uptake in hippocampal slices of mice treated with corticosterone. However, the glutamate uptake in cerebral cortical slices was not altered in mice exposed to corticosterone. The Na+K+ATPase and AChE activities were not changed in the hippocampus or cerebral cortex of mice treated with corticosterone. There were no signs of safety in (p-ClPhSe)2-treated mice in the evaluated parameters. This organoselenium compound reversed the memory impairment associated with stress caused by corticosterone and modulated glutamate uptake in mice.